Haemophagocytic lymphohistiocytosis in inflammatory bowel disease with virus infection - Li, Yuan; Xia, Xuefeng; Zhang, Jing; Song, Zhiqiang; Zhou, Liya; Zhang, Yaopeng; Huang, Yonghui; Shi, Yanyan; Quigley, Eamonn M.M.; Ding, Shigang (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Patients with inflammatory bowel disease (IBD) are at risk of developing haemophagocytic lymphohistiocytosis (HLH) because of chronic systemic inflammation as well as exposure to immunosuppressive medications. The two main causes of HLH in IBD patients are infection with cytomegalovirus and Epstein-Barr virus. Patients with Crohn’s disease are more susceptible to HLH than those with ulcerative colitis. The majority of cases are seen in people receiving an immunosuppressive regimen that included thiopurines.